The Effectiveness of Village Government on Theological-Based Drug Eradication in Cermin Kiri Village Beach, Sub-District Mirror Beach - Ashar, Yulia Khairina; Rismayani, Fanya Audi; Hasrimy, Nabila Felicia; Hasibuan, Khairunnisa; Harahap, Hadi Wahyudi; Parinduri, Muhammad Rafli (Jurnal Abdi Mas Adzkia, 2024)
The number of drug cases in Cermin Kiri Village Beach tends to increase, this occurs because community participation and awareness of drugs is still lacking. Drug abuse is one of the prohibitions in Islam. Inhaling drugs can damage the mind, and we are obliged to protect our minds because the mind is a source of responsibility for a servant of Allah SWT. In addition, geographical and environmental factors also support drug smuggling and transactions. The purpose of this study is to determine the role of government and society in drug cases that occur in Pantai Cermin Kiri Village and how to overcome them. The method used is descriptive qualitative method, which is by collecting information through observation in-depth interviews and other information related to this research. The researcher's review sees that the role of the government and the community is to form an IBM unit that handles drug cases in this village, with the holding of the Desa Bersinar (Clean from Drugs) program having a good impact on the village by approaching the IBM Unit which conducts socialization to convey the dangers of drugs and how to overcome them. The head of the IBM unit, who is a religious figure in the village, approaches the understanding of Islamic theology for drug addicts in social and religious behavior. Based on the existence of religious knowledge taught both by the family and by religious leaders, it is a spiritual approach to get closer to God in order to rebuild moral character, and is considered capable of treating various kinds of diseases of the body and soul.